PENGARUH GAYA KEPEMIMPINAN BERORIENTASI PRESTASI TERHADAP KINERJA DENGAN VARIABEL MODERASI PARTISIPASI PENGAMBILAN KEPUTUSAN DAN NEED FOR ACHIEVMENT - Widiyanti & Suprayitno (Universitas Slamet Riyadi, 2012)
ABSTRACT The design of this study is research conclusive causal or causal relationship with the primary objective to test a certain influence. in this study the relationship is evidenced by multiple linear regression modeling research is conclusive. This research method uses census, the studies using the entire population as a sample. The variables studied include: achievement-oriented leadership style, participation in decision making, need for Achievement, participation in decision-making and employee performance. The conclusions obtained in this study were: achievement-oriented leadership style affect employee performance significantly, participation in decision-making moderating influence achievement-oriented leadership style on employee performance significantly, the need for achievement moderating influence on achievement-oriented leadership style on employee performance significantly. Keywords: leadership style, need for achievement, participation in decision-making, performance.